Online Marketing Strategy of Tourist Attractions to Increase The Number of Tourist Visits - Hasni Hasni; Dwi Agustyawati; Rusdin (Journal of Society, Community and Business Development, 2023)
Indonesia is known as a country that has thousands of tourist destinations. No wonder this makes the tourism sector one of the main foreign exchange contributors for Indonesia. Apart from being a source of foreign exchange, tourism also plays a major role in the economic, social, entrepreneurial and cultural fields. The covid 19 pandemic that has hit the world including Indonesia in recent years has an impact on the amount of income in the tourism sector. Some of the problems faced in the management of tourist attractions in Lawela Selatan Village are: 1) the number of tourists visiting the tourist attraction is still relatively small and only comes from the neighborhood around the village due to the lack of marketing carried out by the manager of the tourist attraction, 2) Not all target partners understand about online marketing strategy management, 3) not all target partners are technology literate and able to maximize information technology so that the promotion carried out is still minimal, 4) The amount of content through social media is still limited, so the marketing reach is not too broad, 5) Kaburaburana tourist attraction does not yet have its own website to introduce its destination to the wider community. This activity was carried out in two stages, namely preparation and socialization. The implementation of PkM activities went smoothly in accordance with the expected objectives. As many as 83% of participants have a good understanding of online marketing strategies to increase the number of visitors to tourist attractions.